E-cigarettes in ENT: what do we need to know?. Issue 6 (19th April 2016) - Stobbs, N; Lillis, A; Kumar, N
Abstract: Background: E-cigarette use in the UK is increasing and we are commonly encountering patients in the ENT clinic who are e-cigarette smokers. Currently, there is no regulatory body or licensing for e-cigarettes. This means that the contents, and therefore potential carcinogenic and toxic risks, can vary greatly from product to product. Patients are starting to ask about the risks of e-cigarettes and their use in smoking cessation. Objectives: This review aimed to examine the regulations, trends, and carcinogenic and health risks of e-cigarettes, and summarise the evidence for their use in smoking cessation. It also aimed to provide a general awareness regarding the advice and information that can be safely given to patients.